DAMPAK KOMUNIKASI BISNIS TERHADAP KINERJA ORGANISASI DI PERUSAHAAN - Irwan Misbach (Fakultas Dakwah dan Komunikasi, 2016)
The objective of this research is to go into the impact of business communication toward organisation performance in a company. In business, there is a message communicated through some communication channels such as Internet, print media, radio, television, and so forth. It is whether to be reached or not the significant change of organisation performance as an outcome of business communication. This research is done to investigate the relation business communication and organisation performance in the company by applying literatures as research instrument based on a context and to quantify the implication “Construction” which is studied. Applying a survey method, this study collects 100 manufacture companies and services which operate in Makassar. The research instrument shows that reliability and validity are valid. The data is analyzed by descriptive statistic, percent, and examination analysis of ‘t’. This research found out that effective business communication is highlighted on the fair level in the companies which are surveyed. It is also found that there is an effective business communication in the practice level which is related to business categories and its dimensions.